Active vibration control: Design towards performance limit. (15th May 2022) - Wang, Jiqiang
Highlights: A new framework is proposed where the performance is represented through geometric expressions. Important problems of performance limit and compromise are addressed based on visual inspections. Handling of constraints is integrated into the graphical framework. A performance-limit-oriented approach is established providing a new design methodology for active vibration control. Abstract: Active vibration control has been conventionally treated as a disturbance attenuation problem in control-theoretic communities. Such a treatment is not satisfactory, particularly with handling finite-frequency band, tackling performance limit, and analyzing performance compromise issues etc. In this paper, a new framework is proposed where the performance is represented through geometric expressions; the important problems of performance limit and compromise are then tackled based on visual inspections; furthermore, the optimal constrained solutions are also obtained by handling the constraints within the same framework. Consequently, a performance-limit-oriented approach is established providing a new design methodology for active vibration control. A vehicle suspension structure is considered for illustration and validation of the claims.